The Role ofDemographic Variables in Consumer Purchase Decision. A study with reference to Cars in Perak state Malaysia - Ahmed Siyal, Aftab (Universiti Teknologi PETRONAS, 2009)
This project relates to the study of demographic variables associated with consumer purchase decisions of cars in Perak state. The study would be helpful to identify different consumer groups on the basis of demographic variables to optimize the car marketing business in the state. Demographics are used to describe a population in terms of its size, distribution and structure. It is used to fragment a population on the basis of age, gender, marital status, family size, family life cycle, income, occupation, education, religion, race, generation, nationality and social class. Marketers are keenly interested in the size and growth rate of the population in different cities, regions, nations, age distribution, educational levels, household patterns and regional characteristics and movements. Most of the marketers' strategic decision making heavily depend on the demographic variable of people in the region where they focus on marketing their products. Marketers can make better decisions only when they know why and how individuals make their better consumption decisions. They could predict how consumers are likely to react to various informational and environmental aspects and could shape their marketing strategies in such a way that they can achieve a great competitive advantage in the market.